Supramolecular networks stabilise and functionalise black phosphorus. Issue 1 (December 2017) - Korolkov, Vladimir; Timokhin, Ivan; Haubrichs, Rolf; Smith, Emily; Yang, Lixu; Yang, Sihai; Champness, Neil; Schröder, Martin; Beton, Peter
Abstract The limited stability of the surface of black phosphorus (BP) under atmospheric conditions is a significant constraint on the exploitation of this layered material and its few layer analogue, phosphorene, as an optoelectronic material. Here we show that supramolecular networks stabilised by hydrogen bonding can be formed on BP, and that these monolayer-thick films can passivate the BP surface and inhibit oxidation under ambient conditions. The supramolecular layers are formed by solution deposition and we use atomic force microscopy to obtain images of the BP surface and hexagonal supramolecular networks of trimesic acid and melamine cyanurate (CA.M) under ambient conditions. The CA.M network is aligned with rows of phosphorus atoms and forms large domains which passivate the BP surface for more than a month, and also provides a stable supramolecular platform for the sequential deposition of 1, 2, 4, 5-tetrakis(4-carboxyphenyl)benzene to form supramolecular heterostructures. Few-layered black phosphorus has been exploited in transistors and other devices, but its poor stability under ambient conditions remains problematic. Here, a UK-Swiss collaboration show that a monolayer-thick supramolecular hydrogen-bonded network can protect a black phosphorus surface for over a month.